2017
DOI: 10.48550/arxiv.1710.09440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small-mass atomic defects enhance vibrational thermal transport at disordered interfaces with ultrahigh thermal boundary conductance

Abstract: The role of interfacial nonidealities and disorder on thermal transport across interfaces is traditionally assumed to add resistance to heat transfer, decreasing the thermal boundary conductance (TBC). 1 However, recent computational works have suggested that interfacial defects can enhance this thermal boundary conductance through the emergence of unique vibrational modes that are intrinsic to the material interface and defect atoms, 2-6 a finding that contradicts traditional theory and conventional understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, contrary to the crystalline Si/Ge structure, where these types of modes contribute >15% to TIC, the interfacial modes across the Si/SiO2 interface at 16 THz contribute <2% to TIC. These observations substantiate that, contrary to our strong understanding of thermal conductivity, 57 thermal transport across interfaces is much more intricate, 45,58,59 which is why every interface is unique, and any generalization based on prior observations to new and unexplored interfaces might be proven to be incorrect. Regions 2 and 4 are mostly comprised of partially extended modes on the SiO2 side.…”
Section: Textmentioning
confidence: 52%
“…However, contrary to the crystalline Si/Ge structure, where these types of modes contribute >15% to TIC, the interfacial modes across the Si/SiO2 interface at 16 THz contribute <2% to TIC. These observations substantiate that, contrary to our strong understanding of thermal conductivity, 57 thermal transport across interfaces is much more intricate, 45,58,59 which is why every interface is unique, and any generalization based on prior observations to new and unexplored interfaces might be proven to be incorrect. Regions 2 and 4 are mostly comprised of partially extended modes on the SiO2 side.…”
Section: Textmentioning
confidence: 52%
“…More recent work from Giri et al has demonstrated significant enhancement in interfacial thermal transport for a SiOC:H/SiC:H interface through the emergence of high-frequency vibrational modes arising from atomic mass defects at the interface. 49 They were able to demonstrate a TBC approaching 1 GW/m 2 K for this material system.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 90%
“…Generally speaking, phonons with a certain frequency have a high likelihood to transmit through an interface only when phonons with this frequency exist on the other side of the interface or when specific modes that are local to the interface help the transmission of those phonons. [47][48][49][50][51][52] Therefore, the degree of DOS overlap between two adjacent materials has a significant effect on the TBC across an interface. Due to the small mass of carbon atoms and strong bonds among these carbon atoms in diamond, diamond has a very high cutoff frequency (the Debye temperature of diamond is 2230 K).…”
Section: Enhanced Thermal Transport Across Interfacesmentioning
confidence: 99%